REVERSAL OF CISPLATIN-INDUCED MEMORY IMPAIRMENT BY GALLIC ACID IN EXPERIMENTAL RAT MODEL - Patel, Sucharita; HM, Chandan; KL, Krishna; HS, Nandini; Ghosh, Abhinav Raj; AN, Bhooshitha (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to evaluate the protective effect of gallic acid on cisplatin-induced memory impairment (MI) in the rat model. Methods: Five groups of Wistar albino rats (n=6) were employed and the duration of the study was 22 days, excluding the pre-treatment period. Animals were pretreated with gallic acid for a period of 5 days and continued daily (200 mg/kg) for 22 days. The cisplatin (3 mg/kg) was given once in a week for 3 consecutive weeks to induce MI, whereas donepezil was used as standard. The evaluation was done by a change in body weight, memory activity by Morris water maze (MWM), locomotor activity by actophotometer, antioxidant activity by thiobarbituric acid reactive substance (TBARS), glutathione (GSH), and estimation of acetylcholinesterase (AChE) activity in brain homogenate. Results: Administration of cisplatin has induced MI by increasing in escape latency time, decrease in time spent in the target quadrant in the MWM task and it was reversed by gallic acid treatment. Decreased locomotor activity by cisplatin was also increased by gallic acid when tested by actophotometer. Cisplatin administration has induced oxidative stress by increasing TBARS and decreasing GSH levels. Gallic acid due to its proven antioxidant activity reversed the effects of cisplatin. The AChE level was significantly increased in the control group, whereas treatment groups have shown a decrease in AChE level. Conclusion: Gallic acid may serve as a primary agent to treat the cognitive impairment and oxidative stress associated memory dysfunctions. However, more extensive studies are needed before utilization in the clinical trial.